Modified natural rubber solid polymer electrolytes / Siti Nor Hafiza Mohd Yusoff - Mohd Yusoff, Siti Nor Hafiza (2013)
Solid polymer electrolytes comprise of epoxidized natural rubber (ENR) and methylgrafted natural rubber (MG) as polymer hosts added with LiC10₄ were prepared by solution casting technique. Glass transition temperature (Tg) obtained by using differential scanning calorimetry (DSC) and the ionic conductivity evaluated from bulk resistance (Rb) determined using the impedance spectroscopy point towards the higher solubility of the lithium salt in MG rubber. Moreover, two Tgs are observed for the MG-salt electrolyte system whereas only one Tg is obtained for the ENR-salt system at all salt concentrations…